KUALITAS PELAYANAN PT. POS INDONESIA (PERSERO) KOTA DUMAI (Studi Kasus Dalam Pemberian Jasa Paketpos) - Ryan Haryanto; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PT Pos Indonesia (Persero) Dumai is one of the BUMN that are engaged in service trafficnews, money, stuff with the largest service network and has spread in all corners of thecountry. The quality of service to the community is often used as a benchmark in viewing thesuccess of an organizations or Government agencies. The Government as a provider ofservices trying to provide services with the quality that corresponds to the expectations of thecommunity. But in fact the Dumai in particular in the provision of services of paketpos at thepost Office of Dumai have overall perfect in providing service to the community. This can beseen from the large number of complaints about the existing services at the post officeDamai. As for the purpose of this research is to find out how quality of service PT. PosIndonesia (Persero) Dumai in providing paketpos Services.The concept of the theory is thetheory of service quality according to Zeithmal et al in Hardiyansyah. Indicators in this study,namely: Tangibles (Facilities and equipment Service Appearance), Realibility (reliability inService Delivery), Responsiveness (Ketanggapan in the provision of Services), Assurance(the ability of Employees to create Customer Confidence) and Emphaty (Caring Employeesof PT. Pos Indonesia (Persero) Dumai).From the results of research, it can be concluded thatthe services provided by PT Pos Indonesia (Persero) Dumai not optimal. It can be seen theindicator Realibility (reliability) of which telhat from the package that is sent is not up at theright time and couriers in charge of delivering the goods did not show the keramahanya, aswell as PT Pos Dumai has not fully run the SOP. For indicator of Responsiveness(responsiveness) officers from PT. Post not quite responsive in the face of complaints fromcustomers.Key words : service, service quality, Tangibles, Realibility, Respon-siveness, assurancedan empthy